Determinan Produktivitas Tenaga Kerja Industri Mikro dan Kecil (IMK) di Provinsi Bali Tahun 2020 - Kadek Angga Wicaksana; Robert Kurniawan (Politeknik Statistika STIS, 2022)
Labor productivity is an important variable that is closely related to economic growth, competitiveness, and standard of living. However, it turns out that the manufacturing sector in Bali Province has a relatively low level of labor productivity. Therefore, this study aims to identify the variables that affect labor productivity. The analytical method used is a descriptive analysis using tables and graphs inferential analysis using robust regression analysis. The results of the analysis showed that the variable percentage of the workforce who graduated from high school and equivalent, the variable percentage of the male workforce, the variable working hours, the innovation variable, and the raw material variable showed a significant effect affecting the productivity of the IMK business workforce.